2015
DOI: 10.1895/wormbook.1.64.2
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear receptor signal transduction in C. elegans

Abstract: Nuclear receptors are transcription factors that often respond to small molecule metabolites and fat-soluble compounds to regulate gene expression. They broadly govern development, reproduction, metabolism, and homeostasis in diverse metazoan species and their dysregulation is associated with numerous diseases. Work in C. elegans has shed light on the seminal role of nuclear receptors in life history regulation, stem cell progression, developmental timing, cell fate specification, nutrient sensing, metabolism,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 25 publications
1
86
0
1
Order By: Relevance
“…Interestingly, the functions of daf-12 appear to be more conserved with EcR than its apparent fly and vertebrate orthologs, all of which function in lipid metabolism. In both flies and insects, insulin signaling and TGFβ signaling converge with the production of a lipophilic hormone that binds EcR (in the fly) or DAF-12 (in the worm), both of which regulate the let-7 miRNA that in turn mediates major life cycle transitions [89,90]. Interestingly, this pathway may also have a vertebrate analog, whereby estrogen signaling activates the transition to puberty via Estrogen Receptor.…”
Section: Hr96/daf-12/vdr/pxr/car (Nr1ij)mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the functions of daf-12 appear to be more conserved with EcR than its apparent fly and vertebrate orthologs, all of which function in lipid metabolism. In both flies and insects, insulin signaling and TGFβ signaling converge with the production of a lipophilic hormone that binds EcR (in the fly) or DAF-12 (in the worm), both of which regulate the let-7 miRNA that in turn mediates major life cycle transitions [89,90]. Interestingly, this pathway may also have a vertebrate analog, whereby estrogen signaling activates the transition to puberty via Estrogen Receptor.…”
Section: Hr96/daf-12/vdr/pxr/car (Nr1ij)mentioning
confidence: 99%
“…While most of these nuclear receptors have not yet been functionally-characterized, of the dozen or so that have been studied most play some role in regulating metabolism, similar to flies and vertebrates [90]. This includes the well-characterized nuclear receptors nhr-13, -49, -63, -64, -66, -69, -76 , and -80 .…”
Section: Hnf4 (Nr2a)mentioning
confidence: 99%
“…26 In C. elegans, the NHR family has expanded to include 284 members, many of which are derived from a single ancestor, the hepatocyte nuclear factor 4 (HNF4). 27,28 In a recent study, we identified a group of NHRs that are essential for the longevity of germline-ablated worms. Of these, NHR-49 produced the most striking lifespan phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 The degree of equivalence between NHR-49 and PPARa is currently unclear, but in view of their similar activities, and for clarity and convenience, NHR-49 is referred to as the functional homolog of PPARa, here and in other studies. 27,[31][32][33] PPARa is a key regulator of fatty-acid b-oxidation and a member of the PPAR family that also includes other modulators of energy metabolism. 34 nhr-49 was first identified as a regulator of mitochondrial b-oxidation genes during development and for inducing the expression of some b-oxidation while repressing others during short-term fasting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation